The evaluation measurement of patellar height in Adam Malik Hospital - M. Rizal Renaldi; Hafas Hanafiah (ITCOMS, 2014)
AbstractIntroduction : Patellar height is a parameter that is increasingly used, given that it expands the knowledge of knee biomechanicsand the physiopathology of knee ailments. In the last few years, a variety of methods have been proposed as ways of definingthe concept of patellar height, usually involving a ratio between radiographic parameters. The objective of this study was toanalyze the methods for measuring patellar height in relation to inter-observer correlation, and correlation of the methods.Method : The study is cross-sectional design. The data were taken from population in Adam Malik Hospital in December 2013,which fulfill the inclusion criteria and had knee joint radiograph in lateral projection. The measurement of patellar height usinginsal-salvati (IS) method, caton-deschamps (CD) method, blackburne-peel (BP) method and plateau-patella angle (PPA)method. The radiographs were analyzed by four observer with different level of experience in the same time. The data wasanalyzed for the correlation of the methods and correlation of the inter-observer.Result : The study demonstrated that blackburne-peel correlated strongly with all three methods. Poorly degree of correlationoccurred in caton deschamps method. Thus, the PPA and IS showed moderate correlation. The evaluation for interobservercorrelation using interobserver kappa coefficient demonstrated high interobserver agreement for PPA followed by BP, CD, andIS.Conclusion : The best correlation between the inter-observer is using PPA method followed by BP. It is because plateaupatellaangle spatially relates the patella to the tibial plateau or joint line, as does the blackburne-peel method.Keywords : patellar height; insal-salvati (IS); caton-deschamps (CD); blackburne-pell (BP); and plateau-patella angle